2020
DOI: 10.12659/ajcr.925060
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Otitis External: Our Experience and Literature Review

Abstract: Case series Patients: Male, 74-year-old • Male, 76-year-old • Male, 77-year-old Final Diagnosis: Malignant otitis externa Symptoms: Edema • facial paralysis • hearing loss • otalgia and major otorrhea in the right ear Medication: — Clinical Procedure: ENT examination Specialty: Otolaryngology Objective: Unusual clinical course Background: Malignant external otiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(49 reference statements)
0
5
0
7
Order By: Relevance
“…Thus, the timely and suitable use of radiologic modalities and management protocol can lead to improved outcomes which in turn can reduce the need for surgical intervention. 15 In addition, it is worth noting, that whilst clinical presentation, diagnosis, and pathophysiology of NOE is well understood, there is still no consensus on the best use of imaging techniques. 16 The availability of latest imaging technology means that clinicians are now able to use more advanced imaging techniques in many parts of the world.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Thus, the timely and suitable use of radiologic modalities and management protocol can lead to improved outcomes which in turn can reduce the need for surgical intervention. 15 In addition, it is worth noting, that whilst clinical presentation, diagnosis, and pathophysiology of NOE is well understood, there is still no consensus on the best use of imaging techniques. 16 The availability of latest imaging technology means that clinicians are now able to use more advanced imaging techniques in many parts of the world.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…In addition, no quinolone toxicity was encountered in human and animal studies (20) (23). Conversely, El-Nasr et al detected P. aeruginosa growth in 65% of the culture samples from 60 patients with malignant otitis externa and found 77% antibiotic resistance in the antibiogram (24). The antibiogram analyses in the current study revealed that 43.3% of the P. aeruginosa and 33.3% of the S. aureus were ciprofloxacin resistant.…”
Section: Discussionmentioning
confidence: 43%
“…La tomografía detecta osteomielitis del hueso temporal (1) , mientras que la resonancia magnética evalúa tejidos blandos circundantes, expansión intracraneal y edema de médula ósea (que precede a la osteítis), ambos son estudios complementarios (3)(4)(5) . El compromiso radiológico de senos paranasales o de la articulación temporomandibular debe alerta la posibilidad de etiología fúngica (12) , la que fue descartada en nuestro paciente.…”
Section: Discussionunclassified
“…Otras técnicas como la tomografía por emisión de positrones tienen una sensibilidad de 96% y especificidad de 91% para el descarte de osteomielitis de base del cráneo (2) . Tal como se hizo y a fin de evitar demora en el inicio del tratamiento, el diagnóstico de OEM podría plantearse ante la presencia de al menos 3 de los siguientes 5 hallazgos (4) : otitis externa persistente; presencia de tejido de granulación en CAE; radiología con osteomielitis en CAE, base de cráneo o compromiso de celdas mastoideas; compromiso de nervios craneales; y Pseudomonas aeruginosa aislada en cultivo de secreción de oído.…”
Section: Discussionunclassified
See 1 more Smart Citation